The role of cytokinin signalling in rice root vascular patterning - Vaughan-Hirsch, John (2018)
The vascular anatomy of rice roots is an important factor in drought tolerance, but little is known about the mechanisms governing its patterning. The Arabidopsis thaliana root vascular tissues are patterned by a mutually inhibitory feedback loop between auxin and cytokinin signalling (Mähönen et al. 2006). Cytokinin signalling in the procambium promotes accumulation of auxin in neighbouring cells which consequently differentiate as xylem. In these cells, high auxin levels promote expression of the pseudo-histidine phosphotransfer protein (PHP) AHP6, an inhibitor of cytokinin signalling (Bishopp et al. 2011). Whereas the root vasculature of Arabidopsis consists of a single xylem axis with phloem poles on either side, that of rice roots show a central metaxylem vessel surrounded by multiple xylem poles, between which are phloem. I hypothesised that the basic interaction between auxin and cytokinin in vascular patterning is conserved between Arabidopsis and rice, but is adapted to enable development of these different tissue patterns. Chemical treatments revealed that auxin and cytokinin are central regulators of root vascular patterning in rice, as is the case in Arabidopsis. In an effort to test whether this conservation extended to individual components of the molecular circuitry, I examined the role of the three OsPHPs, homologues of AHP6. These genes are not auxin inducible and are not able to rescue the Arabidopsis AHP6 mutant, suggesting they do not function in rice root vascular patterning. However, screening known inhibitors of cytokinin signalling for in auxin inducibility in the root tip revealed a subset of the type-A RRs (OsRR1, OsRR6 and OsRR7) are auxin inducible, and were able to rescue the Arabidopsis ahp6 mutant, suggesting these genes may have been recruited to function in the hormonal crosstalk regulating root vascular patterning. Phylogenetic analyses revealed a single amino acid substitution in a conserved region of the PHPs which differs between the dicots and the monocots. To directly determine activity of the OsPHPs, and the relevance of these substitutions, in-vitro phosphotransfer assays were performed. Preliminary results suggest these substitutions do not affect protein function. To characterise candidate genes, transcriptional reporters and mutant plants were generated. Reporters show expression of most candidate genes in the root, with some localised to root protoxylem. Mutants were generated using CRISPR and homozygous and heterozygous mutants were identified. Together, results described here give insight into how regulatory networks may be adapted to bring about differing responses.